Additional mutations in IDH1/2‐mutated patients with acute myeloid leukemia. (16th July 2021) - Lu, Jingtao; Chen, Meiyu; Hua, Haiying; Qin, Wei; Zhang, Ri; Lu, Xuzhang; Chao, Hongying
Abstract: Objective: Somatic mutations in isocitrate dehydrogenase 1 and 2 (IDH1 and IDH2) frequently emerge in acute myeloid leukemia (AML), but the clinical features and molecular characteristics of IDH mutational status and other coexisting mutations have not been investigated in a large extensively characterized AML series. The aim of this study was to gain insight into the mutational profile of IDH‐mutated patients, such as the frequency and clinical characteristics of coexisting mutated genes. Materials and Methods: We investigated 485 newly diagnosed AML patients (range 18‐81 years). DNA was extracted from bone marrow samples at the time of diagnosis. All samples were investigated with a panel of 49 mutational genes using next‐generation sequencing (NGS). FLT3‐ITD, NPM1, and CEBPA mutations were detected by Sanger PCR sequencing. Results: We found 84 patients (17.3%) with IDH1 or IDH2 mutations. There were 40 IDH1 R132, 15 IDH2 R140Q, 17 IDH2 R172K, and 12 uncommon mutations. No patient was found to have both IDH1 and IDH2 mutations. Patients with IDH2 R140Q mutations were more frequently older and presented with significantly lower average platelet counts, while IDH2 R172K ‐mutated patients had significantly lower white blood cell (WBC) counts. On the background of IDH mutations, the presence of a normal karyotype showed a balanced distribution. The four most frequently coexisting mutated genes were NPM1, DNMT3A, TET2, and FLT3‐ITD. The majority of coexisting mutated genes were involved in regulating transcription and DNA methylation. IDH mutation status had no effect on the CR rate, regardless of other molecular abnormalities. Conclusion: Isocitrate dehydrogenases mutations are associated with a complex coexisting mutation cluster in AML. Future investigation is needed to reveal the association between IDH mutations and other genetic abnormalities, which may have an impact on the progression and prognosis of disease.